Why is there resistance to works councils in Germany? An economic perspective - Steffen Müller; Jens Stegmaier (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
Recent empirical research generally finds evidence of positive economic effects of works councils, for example with regard to productivity and - with some limitations - to profits. This makes it necessary to explain why employers' associations have reservations against works councils. On the basis of an in-depth literature analysis, we show that beyond the generally positive findings, there are important heterogeneities in the impact of works councils. We argue that those groups of employers that tend to benefit little from employee participation in terms of productivity and profits may well be important enough to shape the agenda of their employers' organisation and even gained in importance within their organisations in recent years. We also discuss the role of deviations from profit-maximising behaviour like risk aversion, short-term profit maximisation, and other non-pecuniary motives, as possible reasons for employer resistance.
urn:nbn:de:gbv:3:2-81123
Keywords: J5; 330; employers' association; plant level employee participation; works council